Long-Term Health Outcomes of Infantile Spasms Following Prednisolone vs. Adrenocorticotropic Hormone Treatment Characterized Using Phenome-Wide Association Study - Baker, Monika; Mason, Clint C.; Wilkes, Jacob; Sant, David; Sweney, Matthew; Bonkowsky, Joshua L. (Frontiers in Neurology, 2022)
Objective To determine differences in long-term health and neurological outcomes following infantile spasms (IS) in patients treated with adrenocorticotropic hormone (ACTH) versus prednisolone/prednisone (PRED). Methods A retrospective, case-control study of patients with an ICD-9 diagnosis of IS identified over a 10 year period from a national administrative database. IS patients treated with ACTH or PRED were determined and cohorts established by propensity score matching. Outcomes, defined by hospital discharge ICD codes, were followed for each patient for five years. Related ICD codes were analyzed jointly as phenotype codes (phecodes). Analysis of phecodes between cohorts was performed including with phenome-wide association analysis. Results 5,955 IS patients were identified; analyses were subsequently performed for 493 propensity score matched patients each in the ACTH and PRED cohorts. Following Bonferroni correction, no phecode was more common in either cohort (p < 0.001). However, assuming an a priori difference, one phecode, Abnormal findings on study of brain or nervous system (a category of abnormal neurodiagnostic tests), was more common in the PRED cohort (p <0.05), and was robust to sensitivity analysis. Variability in outcomes were noted between hospitals. Significance We found that long-term outcomes for IS patients following ACTH or PRED treatment are very similar, including for both neurological and non-neurological outcomes. In the PRED-treated cohort there was a higher incidence of abnormal neurodiagnostic tests, assuming an a priori statistical model. Future studies can evaluate whether variability in outcomes between hospitals may be affected by post-treatment differences in care models.